Cardiovascular Reactivity: its Association with Physical Activity, and Some Hemodynamic and Anthropometric Variables - Milagros Lisset León Regal; Rosmari Álvarez Hernández; Mikhail Benet Rodríguez; Cynthia Olivia Morales Pérez; Rachel Yanes Seijo; José Omar de Armas García (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Background: several studies show the influence of physical activity as a protective factor of the cardiovascular system. New evidence forcorroborating this are needed to ensure the prevention of cardiovascular disease. Objective: to determine the relationship between cardiovascular hyperactivity, physical activity and some homodynamic and anthropometric variables in normotensive individuals. Methods: a descriptive correlational cross-sectional study was conducted. The universe of the study consisted of the population between 15 and 74 of the municipality of Cienfuegos in 2010, the sample was 644. The variables were considered: sex, skin colour, age, height, weight, index of body mass, abdominal waist, blood pressures: systolic, diastolic, average and differential (basal and sustained weight test) and physical activity. Pearson Chi- square test was calculated and t was applied for comparison of average independent samples with a significance level of p = 0,05. Prevalence ratios were determined with a confidence interval of 95 %. Results: the prevalence of cardiovascular hyperactivity was higher in the group of 65-74 years and males. Cardiovascular hyperactives showed values of the average hemodynamic variables studied cardiovascular over normoreactive. There is an association between physical activity and better cardiovascular response in normal weight individuals. Conclusions: there is an association between increased blood pressure and obesity in cardiovascular hyperactivity. Physical activity is associated with cardiovascular normoreactivity in normal weight.